Origins of Reform Resistance and the Southern European Regime - Friedrich Heinemann; Theocharis Grigoriadis (WWWforEurope, 2013)
This analysis deals with reform obstacles in general and with the particular challenges of institutional change under the conditions of Southern Europe in particular. It presents a survey on the possible drivers of reform resistance. This includes very different qualities of approaches ranging from classical economics and political-economic explanations to more innovative explanations linked to behavioral econom-ics. This classifying approach on potential reform obstacles is novel with respect to its broadness and systematization and offers a basis for the measurement and empirical testing. The subsequent part analyzes qualitatively and quantitatively to which extent the “Southern European regime” may imply a particular relevance of some of the potential reform obstacles classified before. While a generalization on common factors is always at risk of oversimplification, the literature clearly points towards some relevant similar-ities which contrast the southern EU member countries with the rest of Europe. Reform ability profiles quantify several of the reform obstacles (or reform drivers) to compare EU countries in their likely reform predisposition. These profiles confirm par-ticular Southern European weaknesses which tend to reduce the political-economic feasibility of long-term reforms: a low effectiveness in poverty protection, high inter-temporal discounting and uncertainty avoidance, a poor information level of the popu-lation and deeply shattered trust in national institutions. In a microeconometric analysis based on Eurobarometer survey data, the analysis leaves the highly aggregated level and looks into the individual heterogeneity in reform acceptance. It is shown that several of the reform obstacles identified in theory are also empirically correlated with the individual inclination to accept reforms. The perception of procedural fairness (i.e. satisfaction with the way democracy works) to-gether with trust are the keys for the acceptance of reforms. The impression that out-siders, contrary to theoretical expectations, do not push hard for institutional change is confirmed by the micro-data. These findings are not only helpful to understand the difficulties and constraints of reform strategies. They may also back the development of more convincing crisis strategies. At least for those countries where the trust in national elites, public admin-istration and the democratic system is almost fully eroded, a strong European in-volvement in guiding the reform process may help to foster acceptance. Of course, this only holds as long as the EU institutions have a trust advantage over national institu-tions – which empirically seems to be the case for some Southern European countries. Furthermore, there is a clear priority for a particular reform of the Southern European welfare state which should accompany the otherwise required cutback of benefits and privileges. This priority relates to a system of an effective poverty protection. Without a credible minimum insurance system it is unrealistic to expect that important groups of the population are willing to give up their old privileges. Finally, an important chal-lenge is to win the support of current outsiders whose reform supporting potential is so far not being realized.
Keywords: D7; D8; H3; O1; P2; P3; 330; Behavioural economics; Eurobarometer; European debt crisis; reform resistance; trust